Attention to the macroeconomy - Sebastian Link; Andreas Peichl; Christopher Roth; Johannes Wohlfart (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2023)
Attention to the economy plays a key role in canonical macro models, yet its empirical properties are not well understood. We collect novel measures of attention to the economy based on open-ended survey questions. Our measures are included in tailored panel surveys of German firms and households, conducted before and during a large shock to inflation. Using these new datasets, we provide three sets of stylized facts. First, we describe the cross-sectional and time variation in attention to different aspects of the economy. Attention to the macroeconomy is characterized by large and persistent cross-sectional heterogeneity, responds strongly to changes in the economic environment, and is negatively correlated with attention to household- or firm-level topics. Second, we explore the link between attention and expectation formation. More attentive respondents are more likely to adjust inflation expectations during the shock, have higher confidence in their beliefs, and hold smaller misperceptions about realized inflation, yet their expectations about future inflation deviate more strongly from professional forecasts. Third, we study the role of experiences as a potential driver of attention. Consistent with similarity-based recall, individuals with past experiences of adverse inflation outcomes pay more attention to inflation in response to the shock.
Keywords: D83; D84; E71; 330; Attention; Expectation formation; Experiences; Inflation